Phthalate exposure from drugs during pregnancy and possible risk of preterm birth and small for gestational age. (September 2019) - Broe, Anne; Pottegård, Anton; Hallas, Jesper; Ahern, Thomas Patrick; Lamont, Ronald Francis; Damkier, Per
Abstract: Background: Phthalates are chemical compounds present in a wide range of consumer products and are thought to be endocrine disruptors. Though not commonly known, phthalates are present in some medication with previous studies finding up to 50-fold higher urinary metabolite concentrations among exposed compared to the general population. Previous studies on environmental phthalate exposure and pregnancy outcomes have been contradictory and inconclusive and all previous studies have assessed phthalate exposure using biomarkers despite a known rapid metabolism of phthalates. Objective: To determine whether phthalate exposure from pharmaceutical drugs have effects on preterm birth (PTB) and small for gestational age (SGA). Study design: We conducted a nested case-control study among women in Denmark with a recorded singleton birth and included women who conceived between January 1st, 2004 and December 31st, 2015. To mitigate drug effect and confounding by underlying disease we included pregnancies exposed to selected study drugs, and compared pregnancies exposed to phthalate containing drugs to pregnancies exposed to phthalate free generic drugs. Using Danish health registries, we identified 30, 899 singleton pregnancies exposed to study drugs available in both phthalate-containing and phthalate free versions. Using conditional logistic regression, we estimated associations between phthalate exposure and the risk of PTB and SGA. Birth weight according to gestational age was defined by INTERGROWTH-21st (SGA-I) and by Marsal's equation (SGA-M) for expected birthweight. Results: We included 1965 PTBs, 1315 SGA-Is, and 891 SGA-M cases, matched to 19, 537, 12, 008, and 7573 controls, respectively. Orthophthalate exposure during the third trimester was positively associated with PTB with a crude OR of 1.36 (95% CI: 1.06–1.76). The association was mainly due to diethyl phthalate. Exposure to phthalate polymers in third trimester was associated with a risk of PTB with crude ORs of 2.08 (CI: 1.16-3.71. No associations were found between orthophthalate or phthalate polymer exposure and SGA. Conclusion: Exposure to some phthalate-containing pharmaceutical drugs during third trimester is associated with preterm birth.